Game Edukasi Berbasis Augmented Reality untuk Mengajarkan Konsep Geometri Pada Siswa SD Menggunakan Unity 3D - Muhammad Devano Danendra Hansfawwazi Al-Ghifari; Endah Sudarmilah (Jurnal Media Computer Science, 2026)
Mathematics, particularly geometry, is often considered difficult to understand by elementary school students due to its abstract nature and the high level of spatial visualization it requires. The low interest of students in learning mathematics indicates the need for more innovative and enjoyable learning approaches. This study aims to develop a learning medium based on Augmented Reality (AR) in the form of an educational adventure game to help students understand geometric concepts visually and interactively. AR technology was chosen for its ability to display three-dimensional objects in the real world, thereby enhancing students' spatial understanding. The application integrates elements of a 2D platformer game and interactive quizzes aligned with the Kurikulum Merdeka, and is intended for students in grades IV to VI of elementary school. Enemy characters are designed to resemble geometric shapes to make it easier for students to recognize the forms in a fun way. The AR feature enables 3D visualization of the shapes, complete with names and formulas. The development process follows the Game Development Life Cycle (GDLC), consisting of six stages: initiation, pre-production, production, testing, beta, and release. Black-box testing showed that all 24 features and buttons functioned as expected, achieving a 100% success rate. Usability evaluation was conducted using the System Usability Scale (SUS) questionnaire involving 26 students from MI MPK Kertonatan, resulting in an average score of 69.61. This score falls into the marginal - high category (Grade D) and was rated ok by the users. This AR-based learning media is considered feasible to use and has the potential to enhance students’ interest and understanding of geometric concepts interactively.